Preparing Future Skills and Professional Communication Skills - Eka Dian Savitri; Ni Gusti Made Rai; Aurelius Ratu (Institut Teknologi Sepuluh Nopember, 2020)
Some literature studies showed that to get a better career in the contemporary work environment, students need to develop critical thinking skills, problem solving, emotional intelligence, teamwork, and communication. There is, however, in fact a doubt that educational institutions do not sufficiently provide the needed skills to cope with work competition. While World Economic Forum 2020 indicated about 15 skills that have increasing demand in workplace, educational institutions show slow responses toward the demand which means that students might obtain these skills in the context of non-academic learning process. Some of these skills such as critical thinking analysis, complex problems solving, and analytical thinking and innovation has become the prerequisite skills for the today career. Thus, students need to prepare themselves by increasing the knowledge and skills needed in the future. In virtue of the work demands, educational institutions need to design their curriculum in accordance with the work environment as to be able in bridging a transition from school to work environment.